RF - Organization of a Dermatology Department during the COVID-19 pandemic (2020)
Some dermatology departments have written about their experience during the current pandemic. In Italy, a dermatology clinic postponed visits, treating only urgent cases. The reduction in routine activities allowed reallocation of staff to care for COVID-19 patients.1 A similar approach was adopted by the dermatology department of the West China Hospital, Sichuan University: care was provided via telephone consultations, allowing for a reduction in the flow of patients attending the clinic. Patients wore masks and had their temperature taken before entering the clinic, and doctors wore masks, surgical caps, protective suits, gloves, and goggles throughout the working day.2 At the Sun-Yat-sen University Hospital in China, staff received training in protective measures and facilities were regularly disinfected, resulting in a COVID-19 infection rate of 0% in the dermatology department.